Useful entomocomplex soybean field - Berezovska-Brygas, V.V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
Studied taxonomic structure and number entomophags soybeans in terms of field experience. Established regulatory ability of predatory and parasitic insects. The maximum amount has been fixed at the stage of formation of beans. It has been determined that the ratio «predator : prey» according to the available amount entomophags unable to restrain the proliferation of the number and reduce it to the level economic threshold of harmfulness.